EFFECT OF RATTAN BARK NANOFIBER MICROSTRUCTURE WITH HIGH ENERGY MILLING METHOD TO QUALITY MECHANICAL BIOCOMPOSITES - F.N. Ferdiyan (Jurnal Biofisika, 2012)
Rattan bark fiber is waste of raw rattan production activities. It usually used for roofing houses and strap goods in the traditional markets. Rattan bark fiber containing about 40% cellulose, which was potential to be used as filler for composite applications. Nanotechnology based nanoparticles with High Energy Milling (HEM) has been applied in this research to find the optimum particle size to be implemented as automotive component filler. Three HEM has been applied (1 hour, 5 hours, and 10 hours), and without HEM (0 hours) as control. Measurable particle size is the size of the single particle. Data in the form of particle size distributions, intensity, number and volume of distribution, so it can be assumed to describe the overall condition of the sample. The result shows that 5 hours milling produce the smallest particle size (16.22 nm) and z averages (129.78 nm). Particle Size Analy zer (PSA) results was related to the Scanning Electron Microscopy (SEM) images of 5 hour milling, particle become smaller and look the same or homogeneous as balls. These results indicate that the cellulose in the form of three-dimensional nanoparticles is spherical, and the mechanical tests show that biocomposite rattan bark fiber performance was highest among the other natural composites (kenaf, acacia, water hyacinth, banana, coconut).